Nature exposure might be the intervention to improve the self-regulation and skilled performance in mentally fatigue athletes: a narrative review and conceptual framework - Sun, He; Soh, Kim G.; Roslan, Samsilah; Norjali Wazir, Mohd Rozilee Wazir; Mohammadi, Alireza; Ding, Cong; Zhao, Zijian (Frontiers Research Foundation, 2022)
Background: Due to causing inability of self-regulation (ego depletion) and executive functions such as directed attention and visual searching for relevant information (e.g., the ball location and the position of teammates), mental fatigue impairs skilled performance in various sports. On the other hand, natural scenes could improve directed attention, which may considerably benefit visual searching ability and self-regulation. However, nature exposure as a potential intervention to improve skilled performance among mentally fatigued athletes has not been discussed thoroughly. Purpose: To propose the potential intervention for the impairment of skilled performance among mentally fatigued athletes and generate a framework for future studies. Methods: A narrative review was applied to search broadly across disciplines, retrieving literature from several databases (PubMed, Web of Science, Scopus, and EBSCOhost). Results: Thirty-three works of literature including 39 experiments (mental fatigue 15; ego depletion 5; and nature exposure 19) were obtained. Finally, a conceptual framework was built regarding the effect of nature exposure intervention on skilled performance in athletes for future studies. Conclusion: Three theories (the psychobiological model of exercise performance, the strength model of self-regulation, and attention restoration theory) could be potentially integrated to be a conceptual framework and explain the mechanism of preventing prior mental exertion (e.g., mental fatigue and ego depletion). Future studies could examine more on the duration of the intervention.